Message - Al-Shamahy, Prof. Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2024)
With great pleasure, we would like to congratulate all of the staff and members of the Universal Journal of Pharmaceutical Research (UJPR) on their accomplishments in the field of scientific publishing. The UJPR’s primary objective is to continuously improve in order to fulfill the standards of scientific publishing. In recent years, it has made significant progress in this regard by supporting the publication of high-caliber scientific articles that span a wide range of pharmaceutical and medical studies in many sectors. I anticipate greater success in getting our journal included in prestigious indexes like Scopus. Following this welcome, I will write about the significance of the author’s face image presentation in the journal, so that readers and research colleagues throughout the globe can identify her/him. It is well established that facial expressions are required for conscious or unconscious emotional expression. Rejection is indicated by a frown. Generally speaking, a smile indicates happiness. "The fundamental basis of empathy and the ability to interpret a person’s reactions and predict the likelihood of subsequent behaviors" is the capacity to read emotions in another person’s face. Individual differences in face features and expression are largely attributed to the role that facial muscles play in emotion expression. Psychologists contend that the face has significance inherent in its shape rather than being merely a compilation of traits. This supports the idea that an image is perceived as a whole rather than as a collection of fragments. Additionally, studies show that specific brain regions react favorably to faces. "When viewing pictures of strangers, shy adults showed significantly less activity in the fusiform gyrus than sociable adults." The fusiform face area, located within the fusiform gyrus, is engaged by faces and is activated differentially in shy and sociable persons. Additionally, a different study found that specific brain regions react more strongly to an attractive face: "A widely distributed neural network that includes perceptual, decision-making, and reward circuits is excited by facial beauty." Therefore, the "face" of a system with an internal structure is everything that is visible to the outside world, like a building’s facade. A press or public relations representative, for instance, could be referred to as the "face" of the company they work for. An anonymous person is occasionally referred to as "faceless" since "face" is associated with uniqueness and is used figuratively in social contexts to denote reputation or status. For this reason, the UJPR feels that the scientists that published their study shouldn’t be faceless/nameless; rather, they should be recognized as successful and famous in world society, and as such, their images ought to be on show.